Applying improved median linkage heuristic for cell formation problem considering binary data. (26th July 2011) - Ghosh, Tamal; Dan, Pranab K.
The crucial problem in cellular manufacturing system (CMS) is to identify the machine cells and corresponding part families to form the production cells. This article portrays a novel approach based on median linkage clustering (MLC) algorithm to form the production cells. The projected technique is demonstrated in two portions. Firstly, the MLC procedure and Nei and Li's similarity coefficient method are incorporated to obtain the machine cells. Thereafter, a modified part assignment technique is recommended to form the corresponding part-families. The proposed technique is shown to outperform the other published methodologies and produced improved solutions for the test datasets.